Meningkatkan Aktivitas Dan Prestasi Belajar Peserta Didik Tentang Menghitung Volume Prisma Segitiga dan Tabung Lingkaran Dengan Menggunakan Model Pembelajaran Kooperatif Type Think Pair Share - Naruson Naruson; Ikhsan Ikhsan; Syahril Chaniago (Universitas Pakuan, 2023)
INCREASING STUDENTS' LEARNING ACTIVITIES AND ACHIEVEMENTS ABOUT CALCULATING THE VOLUME OF TRIANGLE PRISMS AND CIRCLE TUBE USING THE THINK PAIR SHARE TYPE COOPERATIVE LEARNING MODEL Abstract. This study aims to determine the Cooperative learning model of the Think Pair Share type can increase the activity and learning achievement of students in the mathematics subject of calculating the volume of triangular prisms and circular tubes in Class VI B SD Negeri Kertamaya, South Bogor District, Bogor City Semester 1 of the 2018 Academic Year/ 2019. To define the process of increasing activity and learning achievement of students in Mathematics of calculating the volume of triangular prisms and circular tubes after applying the Type Think Pair Share Cooperative learning model in Class VI B SD Negeri Kertamaya, South Bogor District, Bogor City Semester 1 of the 2018/2019 Academic Year. To measure the magnitude of the increase in activity and learning achievement of students in mathematics lessons about calculating the volume of triangular prisms and circular tubes after using the Cooperative learning model type Think Pair Share in Class VI B SD Negeri Kertamaya, South Bogor District, Bogor City Semester 1 of the 2018/2019 Academic Year. The results of this study indicate that using the Cooperative learning model of the Think Pair Share type can be a fun variation of learning for students, so it is proven to increase the activity and learning achievement of students in Class VI B SD Negeri Kertamaya, South Bogor District, Bogor City. Before using the Cooperative learning model type Think Pair Share, activities and learning achievement of students only reached an average value of 64.50 then; there was an increase after using the Cooperative learning model type Think Pair Share to 73.25 in cycle 1 and 81.37 in cycle 2 From the description above, the researcher concludes that the use of the Cooperative learning model type Think Pair Share is fun so that there is an increase in the activity and learning achievement of students. Therefore the researchers suggest the Cooperative learning model type Think Pair Share is disseminated and used as an alternative to learning mathematics in schools within the Bogor City Education Office